2017
DOI: 10.1002/nau.23351
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of transcutaneous tibial nerve stimulation (TTNS) for adults with overactive bladder syndrome: A systematic review

Abstract: Limited evidence is provided that TTNS is an effective, safe intervention for idiopathic OAB in adults and may be of benefit in those with neurogenic OAB. Further studies are essential to confirm these results as well as to determine efficacy and associated costs for specific patient groups, most effective stimulation dosage, duration of effect, and stimulation regimes for longer-term maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
85
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 54 publications
9
85
2
1
Order By: Relevance
“…The stimulation could be delivered to the posterior tibial nerve through two distinct routes: using a fine needle (percutaneous‐PTNS) or using a surface electrode (transcutaneous‐PTNS). While sham‐controlled randomized trial (RCT) supporting the use of each of these two approaches for OAB do exist, the worldwide spread of transcutaneous‐PTNS remains more limited despite significant possible advantages such as lower invasiveness and costs . In their manuscript, recently published in NeuroUrology and Urodynamics, Ramirez‐Garcia et al reported the first head‐to‐head randomized controlled comparison of transcutaneous and percutaneous PTNS in overactive bladder (OAB) patients …”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The stimulation could be delivered to the posterior tibial nerve through two distinct routes: using a fine needle (percutaneous‐PTNS) or using a surface electrode (transcutaneous‐PTNS). While sham‐controlled randomized trial (RCT) supporting the use of each of these two approaches for OAB do exist, the worldwide spread of transcutaneous‐PTNS remains more limited despite significant possible advantages such as lower invasiveness and costs . In their manuscript, recently published in NeuroUrology and Urodynamics, Ramirez‐Garcia et al reported the first head‐to‐head randomized controlled comparison of transcutaneous and percutaneous PTNS in overactive bladder (OAB) patients …”
mentioning
confidence: 99%
“…These findings were observed while the same regimen of stimulation was used in both groups, that is, weekly sessions of 30 min for 12 weeks. There is a great heterogeneity in the stimulation regimen and volume of hours in the transcutaneous PTNS literature and the program used in this study duplicated the one from several previous randomized controlled trials . However, one may argue that one of the main asset of transcutaneous PTNS was left aside by using such stimulation regimens.…”
mentioning
confidence: 99%
See 3 more Smart Citations